A time of sifting mystical marriage and the crisis of Moravian piety in the eighteenth century - Peucker, Paul 1963- (The Pennsylvania State University Press, 2015)
"Examines the eighteenth-century crisis in the Moravian Church known as the Sifting Time, and the church's subsequent shift from radical beliefs and practices to conservative mainstream Protestantism"--Provided by publisher
Literaturververzeichnis: Seiten 225-241
Keywords: Zinzendorf, Nikolaus Ludwig von -- 1700-1760; Böhmische Brüder; Religiöser Wandel; Pietismus; Brüdergemeine; Moravian Church / History / 18th century; Piety / History / 18th century; Marriage / Religious aspects / Moravian Church / History / 18th century